The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Sustainable Cities 2017
DOI: 10.1201/b19796-6
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Local Climate Change Adaptation and Mitigation Actions: The Role of Various Policy Instruments in a Multi-Level Governance Context

Abstract: Abstract:Recently, considerable focus, e.g., in the fifth IPCC (Intergovernmental Panel on Climate Change) Assessment Report (2014) has been trained on why adaptation and mitigation have not been developed more than at present, with relatively few local government actions taken compared with, for example, more discursive policy agreement on the importance of the issue of climate change. Going beyond a focus on general limits and barriers, this comment suggests that one important issue is that climate change h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The study also contributes to the literature by shedding more light on the importance of the relations across levels of government (see e.g. Keskitalo, 2016;Westerhoff et al, 2011) and of the local contextual factors such as planning practices (see Chu et al, 2017), urban political economic contexts and state-society interactions (Chu, 2018). It brings new insights from the Chinese megacities that are hardly covered in this literature, and yet are already severely affected by climate change impacts and do surprisingly little to mitigate them.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The study also contributes to the literature by shedding more light on the importance of the relations across levels of government (see e.g. Keskitalo, 2016;Westerhoff et al, 2011) and of the local contextual factors such as planning practices (see Chu et al, 2017), urban political economic contexts and state-society interactions (Chu, 2018). It brings new insights from the Chinese megacities that are hardly covered in this literature, and yet are already severely affected by climate change impacts and do surprisingly little to mitigate them.…”
Section: Discussionmentioning
confidence: 80%
“…Multi-level governance perspective underscores that decision-making on policies involves multiple interdependent actors operating at different levels of government, from national to local (e.g. Hooghe & Marks, 2003;Keskitalo, 2010;Keskitalo et al, 2016;Westerhoff et al, 2011). Multi-level governance, thus, provide the canvas for the operation of a spatial planning system, which is "the ensemble of institutions that are used to mediate competition over the use of land and property, to allocate rights of development, to regulate change and to promote preferred spatial and urban form" (ESPON, 2018).…”
Section: The Three I'smentioning
confidence: 99%
See 1 more Smart Citation
“…While adaptation duties have only begun to emerge through the EU's legal framework, in some countries, national legislation obliges subnational jurisdictions to become active in adaptation (Bisaro, Bel, Hinkel, Kok, Stojanovic, & Ware, 2020b; Tompkins et al, 2010). For example, Keskitalo et al (2016) illustrate that Danish municipalities are, per national regulation, required to set up adaptation strategies, even if the national government cannot enforce their implementation, whereas Finnish municipalities are not obliged to develop such strategies. Aguiar et al (2018) found in a survey of local adaptation strategies in Europe that many originated from implementing European and/or national policy.…”
Section: Motivations and Mechanisms Of Adaptation Policy Diffusionmentioning
confidence: 99%
“…For example, the limited powers of local governments and discursive conflicts among networks of state and non-state actors over how to frame climate policy can challenge the ability of cities to take a leading role in climate change planning (Bulkeley and Betsill, 2005; see also Chapter 5). Keskitalo et al (2016), for example, observe that in Nordic countries, limited leadership from national governments has partially contributed to a pattern of soft and voluntary adaptation policy approaches at the local level, and limited observable success in advancing adaptation implementation. The authors argue that this points to the need to integrate adaptation requirements into more traditional regulatory regimes and instruments that can be more directly enforced by the state.…”
Section: Multilevel Governancementioning
confidence: 99%